2006
DOI: 10.1093/ageing/afl005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and outcome of delirium in medical in-patients: a systematic literature review

Abstract: Delirium is common in medical in-patients and has serious adverse effects on mortality, functional outcomes, LOS and institutionalisation. The development of appropriate strategies to improve its management should be a clinical and research priority. As delirium prevalent at hospital admission is a significant problem, research is also needed into preventative measures that could be applied in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
758
8
31

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,000 publications
(837 citation statements)
references
References 24 publications
40
758
8
31
Order By: Relevance
“…1,2 In patients admitted to hospital, around 30-40% of delirium cases are thought to be attributable to modifi able risk factors, and are therefore preventable. 3 Various approaches aimed at minimising the infl uence of risk factors in medical patients have not improved outcomes, and there are no conclusive studies that support pharmacological prophylaxis. 4 Dexmedetomidine is a highly selective α 2 adrenoreceptor agonist that provides anxiolysis, sedation, and modest analgesia with minimal respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In patients admitted to hospital, around 30-40% of delirium cases are thought to be attributable to modifi able risk factors, and are therefore preventable. 3 Various approaches aimed at minimising the infl uence of risk factors in medical patients have not improved outcomes, and there are no conclusive studies that support pharmacological prophylaxis. 4 Dexmedetomidine is a highly selective α 2 adrenoreceptor agonist that provides anxiolysis, sedation, and modest analgesia with minimal respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Delirium predicts longer hospital stay, increases likelihood of discharge to a skilled nursing facility, and is a marker for significant morbidity and mortality. [40][41][42] Cognitive screening, as discussed above, can help determine who is at risk for delirium, and the Confusion Assessment Method (CAM) is becoming more widely used as a bedside screening tool for detecting delirium.…”
Section: Delirium Is a Common But Serious Condition Among Hospitalizementioning
confidence: 99%
“…Since delirium is an acute medical condition, its prevalence can only be studied in hospital settings. A meta-analysis of 42 studies found delirium to be prevalent on admission in 10-31% of medical inpatients, and to occur in the hospital in 3-29% [4]. Fong et al [5] reported that the overall prevalence of delirium in the community is just 1-2%, but in the setting of general hospital admission this increases to 14-24%.…”
Section: Introductionmentioning
confidence: 99%
“…Fong et al [5] reported that the overall prevalence of delirium in the community is just 1-2%, but in the setting of general hospital admission this increases to 14-24%. The incidence of delirium arising during a hospital stay ranges from 6% to as high as 56%, and this incidence is even higher when more-specialized populations are considered, including those in postoperative, intensive-care, subacute and palliative-care settings [4,6,7]. Postoperative delirium occurs in 15-53% of surgical patients over the age of 65 years [8] and among elderly patients admitted to an Intensive Care Unit (ICU) the delirium incidence can reach 70-87% [9].…”
Section: Introductionmentioning
confidence: 99%